The role of temperature in the synthesis of hybrid inorganic–organic materials: the example of cobalt succinates - Forster, Paul M.; Burbank, Andrea R.; Livage, Carine; Férey, Gérard; Cheetham, Anthony K. (Chemical communications (Cambridge, England), 2004)
Five different cobalt succinate materials synthesized from an identical starting mixture using temperature as the only independent variable show increasing condensation and density at higher synthesis temperatures.